Communicating Science and its Spirit: What, Why and How? - Bhargava, Pushpa M. and Chakrabarti, Chandana (2006)
In this presentation, we have endeavoured to discuss the following: (i) What is science and how it is different from technology? (ii) What method does science follow and how it is relevant in everything we do? (iii) Why is it necessary to communicate not only the knowledge of science but also the spirit of science to the people around the world? And (iv) How may one effectively communicate scientific facts and the spirit it generates?